Patient-reported outcomes after discontinuation of long-term topical corticosteroid treatment for atopic dermatitis: a targeted cross-sectional survey - Takahashi-Ando N (Drug, Healthcare and Patient Safety, 2015)
Naoko Takahashi-Ando,1 Mark A Jones,2 Shigeki Fujisawa,3 Rokuro Hama4 1Department of Applied Chemistry, Faculty of Science and Engineering, Toyo University, Saitama, Japan; 2School of Population Health, The University of Queensland, Herston, Queensland, Australia; 3Fujisawa Dermatology Clinic, Tokyo, Japan; 4Japan Institute of Pharmacovigilance, Osaka, Japan Background: Topical corticosteroid (TCS) treatment is widely prescribed for atopic dermatitis (AD). However, TCS treatment is associated with tachyphylaxis, and discontinuation after long-term use may cause exacerbation of symptoms. Some AD patients are reluctant to use TCS. Objective: To evaluate patient-reported short- and long-term outcomes after discontinuation of TCS treatment for AD. Methods: Questionnaires were distributed to adult AD patients (n=1,812) of doctors who did not recommend TCS as first-line therapy for patients who preferred to avoid TCS. Data collected included current TCS use, duration of TCS use, past discontinuation of TCS use, exacerbation of symptoms after discontinuation of TCS use, and limitations to daily activities because of AD. Results: Of 918 respondents, 97.7% had used TCS, of whom 92.3% had experienced discontinuation of TCS use. After discontinuation, 63.9% experienced their most severe AD symptoms ever. The severity of exacerbation of symptoms was significantly correlated with the length of TCS use (P<0.001). Although most respondents who experienced severe exacerbation after TCS discontinuation were not current TCS users, they generally had fewer current limitations to activities than when AD symptoms were at their worst. Conclusion: Adult Japanese AD patients who experience severe exacerbation of symptoms immediately after discontinuation of TCS use generally improve over time. We suggest caution regarding long-term TCS treatment in AD patients.Keywords: adverse effects of corticosteroids, symptom exacerbation, rosacea-like dermatitis